The Impact of a Self-Avatar, Hand Collocation, and Hand Proximity on Embodiment and Stroop Interference - Peck, Tabitha C.; Tutar, Altan (IEEE transactions on visualization and computer graphics, 2020)
Understanding the effects of hand proximity to objects and tasks is critical for hand-held and near-hand objects. Even though self-avatars have been shown to be beneficial for various tasks in virtual environments, little research has investigated the effect of avatar hand proximity on working memory. This paper presents a between-participants user study investigating the effects of self-avatars and physical hand proximity on a common working memory task, the Stroop interference task. Results show that participants felt embodied when a self-avatar was in the scene, and that the subjective level of embodiment decreased when a participant's hands were not collocated with the avatar's hands. Furthermore, a participant's physical hand placement was significantly related to Stroop interference: proximal hands produced a significant increase in accuracy compared to non-proximal hands. Surprisingly, Stroop interference was not mediated by the existence of a self-avatar or level of embodiment.